Quantitative analysis of new drug registration policies for traditional Chinese medicine using the PMC index model - Yiming, Liu; Ming, Xie (Frontiers in Public Health, 2025)
IntroductionTraditional Chinese medicine (TCM) culture represents the essence of traditional Chinese culture. The registration of TCM is crucial for promoting its sustainable development and can significantly contribute to the economic growth of the TCM industry. Consequently, the Chinese government has introduced a series of policies regarding TCM registration, aiming to provide scientific and effective guidance for the innovation, inheritance, and development of TCM. At present, China’s TCM registration policies are still inadequate, and it is necessary to evaluate and compare them quantitatively.MethodsThe present study utilizes text mining methodology and the Policy Modeling Consistency Index (PMC index) model to establish an evaluation system for quantitative assessment and comparison of the Drug Administration Law, Drug Registration Administration Method, Chinese Medicine Registration Administration Method, Chinese Medicine Law, and other relevant legislations spanning from 1985 to 2023.ResultsThis study revealed that (1) through a comprehensive analysis of high-frequency words, different Traditional Chinese Medicine Regulatory Policies (TCMRPs) shared similar content and objectives, but placed varying degrees of emphasis on specific aspects. (2) The average PMC index of 165 TCMRPs was 5.858, which generally fell within the acceptable range. Among these policies, none achieved perfection, while 39 policies were deemed excellent, constituting 23.6% of the total policies. There were a total of 119 policies falling within the acceptable range, accounting for 72.1% of the total. Additionally, there were 7 policies with below-standard performance, making up for only 4.2% of the total. (3) The PMC index values differed significantly across issuing institutions and incentive methods for various TCMRPs, with generally low scores observed in this regard. However, there were similarities in terms of policy nature, timelines, function, content, mode and scientism rating among these policies.Conclusion(1) The TCM registration system requires further enhancement and refinement to ensure greater efficiency and compliance with current standards. (2) Technical problems have hindered the research and development of TCM. (3) Talent preservation should be incorporated as a key consideration in the formulation of TCM registration policies. (4) The formulation of TCM registration policies should incorporate economic incentive considerations. (5) China ought to intensify the development of classic and renowned formulas to expedite the registration of novel TCM.